Ear Reconstruction - Avelar, Juarez M. (Springer International Publishing : Imprint: Springer, 2017)
This book comes to its second edition intending to broaden the discussion about the plastic surgical techniques for the reconstruction of the ear. It features a more in-depth discussion of the topics previously addressed, including chapters on microtia, anotia, the upper pole, auricular lobule and complications during and following ear surgery. Furthermore, it addresses a wide variety of deformities of the auricle and surgical topics that were not included in the previous edition, such as: Reconstruction of the tragus and creation of the external auditory canal - key considerations when planning or performing a reconstruction of the ear. New concepts on the surgical anatomy of the ear - essential knowledge for plastic surgeons when performing the operation. Traumatic amputation of the ear - a common and severe social and organic problem. Discussions are presented that address the cause of the problem, as well as guidelines for surgeons during first aid in order to provide adequate reconstruction. Ear reconstruction for reparation of deformities caused by piercing Reconstruction of the auricle secondarily to prominent ear surgery Reconstruction of the ear after human and animal bite Secondary reconstruction of the ear Reduction otoplasty - an important procedure whenever the size of the ear negatively impacts the patient's wellbeing or self-esteem due to imbalanced facial contours. Features important notes on a procedure that leaves inconspicuous scars and creates a normal and natural appearance of the organ's architecture. Post-operative care - special information on how to optimally avoid complications after surgery. Reconstruction of the ear is required in a variety of patients, especially in those with congenital anomalies and associated deformities or those suffering from accidents and trauma affecting the auricle. In this sense, this surgical approach has the ultimate goal of improving aesthetic and functional aspects of congenital and acquired anomalies of the ear. Throughout the book, the goal is to share the author's experience, gathered in the course of 43 years dedicated to this challenging field. Descriptions and illustrative photos concerning correction and reconstruction of the auricle caused by prominent ear surgery are presented in detail. The didactic approach, supplemented by color illustrations and surgical photos, helps to demonstrate basic and advanced techniques alike. With forewords by Ivo Pitanguy and Jorge Psillakis.
Keywords: Medicine.; Plastic surgery.; elektronické knihy; electronic books